Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Karyawan dengan Kompensasi Sebagai Moderasi di PT. Semarang Autocomp Manufacturing Indonesia - Kurnia Dewi Lestari; Gilang Kharisma Putra (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
The research aims to analyze the influence of work discipline and motivation on employee performance, analyzing the role of compensation in moderating the influence of work discipline and motivation on employee performance at PT. Semarang Autocomp Manufacturing Indonesia. This research approach is to use a quantitative research approach. The data collection technique in this research is by distributing questionnaires and literature study. The population in this study were employees of PT. Semarang Autocomp Manufacturing Indonesia Honda H04 area production department, totaling 100 employees. The number of samples in the research was 100 respondents using nonprobability sampling techniques with saturated sampling techniques and purposive sampling methods. This research uses outer model and inner model analysis using the Structural Equation Model (SEM) technique with the SmartPLS 4.0 program. The research results show that discipline has a positive and significant influence on employee performance, motivation has a positive and significant influence on employee performance, compensation cannot moderate or strengthen work discipline on performance, and compensation cannot moderate or strengthen motivation on employee performance